Myokines: Novel therapeutic targets for diabetic nephropathy - Yang, Ming; Luo, Shilu; Yang, Jinfei; Chen, Wei; He, Liyu; Liu, Di; Zhao, Li; Wang, Xi (Frontiers in Endocrinology, 2022)
With the increasing incidence of diabetic nephropathy (DN), it is very urgent to find effective preventive and therapeutic measures for DN. “The effective exercise is good for health” is a proverb that we often say. However, its beneficial role of exercise in kidney disease, especially DN, and the molecular mechanisms have rarely been reported. In fact, muscle is not only a motor organ, but also an important endocrine organ, which secretes a series of proteins called “myokines” and then circulates to the target organs to play their biological role. In this review, we summarize the currently discovered myokines and their research progress in DN, propose the concept of “muscle-renal axis” for the first time and discuss their potential as a therapeutic target for DN.